Kajian Aspek Moral Pada Buku Kumpulan Dongeng Si Kancil Karya Mb Rahimsyah Ar (Buku Pegangan para Bunda untuk Mendongeng Kepada Si buah hati) - Siti Karomah; Agus Hermawan (Universitas Merdeka Madiun, 2020)
Abstractâ€” Literary work, directly or indirectly, is the realization and imagination of the author as a reflection and the reality that the author gets from society. Literary works can be found through the life forms of society. Thus, literary works cannot be separated from the elements around them. Literary work along its journey always implicate man, humanity, life, and life. In essence, literary works are born for the surrounding community. Literary works are the products of authors who live in the social world. That way, short story literary works in the form of fairy tales are the author's imaginative world that is always related to social life. There are interesting things that are given to our children to change attitudes and daily ethics.Â Keywordsâ€”: Literary works; short stories; fairy tales.